Optimizing The Role of Students in The Context of ‘Mendoan Covid-19’ (Towards Indonesia Coexist With Covid-19) Through The Use Of Social Media - Adlina, Tsabita Zharfa; Fatau, Ade Syafira; Rifti, Wifaqwudd Az-Zahra (International Conference on Sustainable Health Promotion, 2021)
Social media is an essential part of technological development that attracts the most sympathy at various levels of society. From 2016—2019, the use of social media continues to increase. With the stipulation of the COVID-19 pandemic in early 2020, the use of social media to date has reached 4.2 billion. It has become a basic need for the community as a means of communication and the most effective repository of information. This research is a comparative causal quantitative research. Based on observational questionnaire data on 12—14 July 2021 from 100 participants, consisting of 2 age groups 15—21 and >21 years, were analyzed by the Mann Whitney statistical test and showed that there were differences in the use of social media about COVID-19 in the two age groups ( p-value = 0.009) which is also supported by the characteristics of the respondents, including the duration of use of social media, the type of social media and the type of content that is most often use. Students can use social media to provide education and information about COVID-19 to coexist with COVID-19 through the form of audio-visual content on several social media that are of interest based on differences in age groups